2020
DOI: 10.1088/1742-6596/1569/3/032063
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ginger Extract (zingiber officinale roscoe) on the Number of Neutrophil Cells, Fibroblast and Epithelialization on Incision Wound

Abstract: The wound healing process consists of three phases, namely the inflammatory phase, proliferation, and maturation. An increase in the number of neutrophil cells and macrophages signifies an inflammatory phase. Fibroblasts and epithelialization indicate a proliferation phase, whereas in the maturation phase is marked by the occurrence of wound healing. Ginger (Zingiber officinale Roscoe) contains active substances, namely triterpenoids, flavonoids and saponins. Flavonoids function as anti-inflammatory. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The histological results of Group II showed better wound healing compared with that in Group I. These findings are in line with those of a prior studies that showed that ginger administration at various time intervals significantly reduced the number of inflammatory cells, increased the number of fibroblast cells, and improved incisional wound epithelialization [38], [39] . Our results can further be explained by the fact that ginger, besides its ability to treat a variety of conditions, such as cancer, diabetes mellitus, degenerative diseases and cardiovascular diseases like hypertension and atherosclerosis, it also has a unique anti-inflammatory and antioxidative properties [40] .…”
Section: Discussionsupporting
confidence: 90%
“…The histological results of Group II showed better wound healing compared with that in Group I. These findings are in line with those of a prior studies that showed that ginger administration at various time intervals significantly reduced the number of inflammatory cells, increased the number of fibroblast cells, and improved incisional wound epithelialization [38], [39] . Our results can further be explained by the fact that ginger, besides its ability to treat a variety of conditions, such as cancer, diabetes mellitus, degenerative diseases and cardiovascular diseases like hypertension and atherosclerosis, it also has a unique anti-inflammatory and antioxidative properties [40] .…”
Section: Discussionsupporting
confidence: 90%
“…The average recovery took 16 days [ 37 ]. According to Rahayu et al, applying ginger extract to incision-wounded rats reduces neutrophil concentrations in the proliferation and maturation phases [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant activity: Different studies have been showing that 6‐Gingerol present in ginger extract shows its antioxidant action by different mechanisms including inhibition of lipid peroxidation, increasing the activities of intracellular antioxidant enzymes like superoxide dismutase, catalase, and glutathione, decreasing inducible nitric oxide synthase and TNF‐α expression followed by inhibiting activation of nuclear factor‐kappa B inhibitor alpha and NF‐κB in macrophages and by inhibiting the overload of intracellular Ca²⁺ followed by suppressing the mitochondrial membrane disruption and ultimately production of reactive oxygen species 79 . Action on different stages of wound healing: It affects the inflammatory and proliferative phases of wound healing by increasing fibroblasts cell migration, 80 phosphorylating Akt and mTOR, and ultimately Akt/mTOR signaling pathway activation. In the remodeling phase, Ginger extract was found to enhance collagen deposition, faster wound contraction, and increase the rate of re‐epithelialization 74 …”
Section: Wound Healing Activity Of Some Medicinal Plantsmentioning
confidence: 99%
“…76 shows its ability to combat S. aureus bacteria, Pseudomonas aeruginosa, and Escherichia coli by suppressing DNA metabolism, 78 species. 79 Action on different stages of wound healing: It affects the inflammatory and proliferative phases of wound healing by increasing fibroblasts cell migration, 80 phosphorylating Akt and mTOR, and ultimately Akt/mTOR signaling pathway activation. In the remodeling phase, Ginger extract was found to enhance collagen deposition, faster wound contraction, and increase the rate of reepithelialization.…”
Section: Mangosteen (Garcinia Mangostana)mentioning
confidence: 99%